Study on the biodegradation of crude oil by free and immobilized bacterial consortium in marine environment - Chen, Qingguo; Li, Jingjing; Liu, Mei; Sun, Huiling; Bao, Mutai (PLOS ONE, 2017)
Five strains of bacteria, namely, Exiguobacterium sp. ASW-1, Pseudomonas aeruginosa strain ASW-2, Alcaligenes sp. ASW-3, Alcaligenes sp. ASS-1, and Bacillus sp. ASS-2, were isolated from the Zhejiang coast in China. The mixed flora of the five strains performed well with degrading 75.1% crude oil (1%, w/v) in 7 days. The calcium alginate—activated carbon embedding carrier was used to immobilize bacterial consortium. Immobilized cells performed better than free ones in variations of environmental factors containing incubated temperature, initial pH, salinity of the medium and crude oil concentration. The degradation process of crude oil by immobilized bacteria was accelerated compared with that of the free ones. Bacterial consortium showed better performance on biodegradation of normal alkanes than that of PAHs. Improvement of immobilization on the biodegradation efficiency of normal alkanes (31.9%) was apparently high than that of PAHs (1.9%).